Computer system evaluation in robot control - Tenreiro Machado, J. A. (2019)
The high computational burden posed by mordern control algorithms preclude its industrial application using present day microcomputers. In this paper we evaluate the computational load of different logical and arihmetic operations and the capabilities of several computing systems (software & hardware). This study reveals that real-time limitations can be alleviated through the adoption of general techniques achieve not only a more efficient management of the computational resources but also provide a deeper insight on developments towards future real-time control architectures.